Stellar Photometry at the Crossroads of the Two Centuries - Straižys V. (Open Astronomy, 2003)
In the last century photometry was recognized as a powerful method for investigation of physical parameters of stars and of interstellar matter. Photometric investigations now cover the spectral range from the far ultraviolet to the far infrared. The article describes the most important landmarks in development of photometric classification of stars and the number of photometric survey projects accomplished by ground-based and space telescopes and including millions of point sources. The success of the future LSSD and Gaia projects will depend on the use of optimum photometric passbands.